PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL SMK NEGERI KABUPATEN PEMALANG - Khalimah, Siti; Sutomo, Y (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to examine and analyze the influence of motivation and the effect of competence on organizational commitment, the influence of motivation. effect of competence and the effect of organizational commitment on teacher performance. This research locations throughout the SMK in Pemalang. The method used in this research is descriptive analysis method with quantitative approach. The population of this research is 262 teachers of SMK N in Pemalang. 158 teachers of them were as samples who are taken propotionally in each school.To know the effect of independent variables on the dependent variable used multiple linear regression analysis tool. Based on the results of data analysis can be concluded that work motivation has positive and significant effect on organizational commitment. Teacher competency has positive and significant effect on organizational commitment. Work motivation has positive and significant impact on teacher performance. Teacher competent has positive and significant impact on teacher performance. Organizational commitment has positive and significant impact on teacher performance. Based on the results of this study recommended to the parties stakeholders in education at the school level, district level or at the regency level to manage improved performance of teachers as professionals who are competent in their duties. Furthermore, simultaneous and structural need cooperation in synergy to manage the teacher to be better so the teacher can increase the quality of its performance so that the quality of education is also increasing. Keywords: motivation, competence, organizational commitment, Teacher Performance